The Economic Efficiency of Rice Farming Production Factors in Karawang Region - Nurul - Aenunnisa; Zainul Hasan; Nun Maulida Suci Ayomi (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2022)
The population's food needs are increasing during the COVID-19 pandemic. If the pandemic lasts longer, it is feared that a food crisis will occur, because residents will scramble to stock up on food. This study aims to analyze the efficiency level of rice productivity and the determinants that affect rice productivity to face the food crisis. This study uses secondary data and primary data, obtained from interviews. The data analysis method used is the Cobb-Douglas Stochastic Frontier Production Function approach with the Maximum Likelihood Estimation (MLE) method and multiple linear regression, which is obtained using Stochastic Frontier Analysis and E-Views 8 analysis tools. Production of land area, seeds, and pesticides have a significant effect on rice production in Karawang Regency. While the use of production factors of urea fertilizer, NPK fertilizer, SP36 fertilizer and labors workdays did not have a significant effect on rice production in Karawang Regency. The level of technical efficiency in rice farming in Karawang Regency reaches 0.9607 which indicates that rice farming is technically close to efficient. The combination of the use of land area production factors, seeds, urea fertilizer, SP36 fertilizer in rice farming in Karawang Regency has not yet reached the optimal point that is economically efficient. The level of elasticity of production in rice farming in Karawang Regency reaches a value of 1.3971 so that rice production has a scale that is increasing return to scale.